Merkel cell polyomavirus in lung carcinogenesis: evidence and controversy - Zhou, Changlong; Lu, Liang; Hu, Maohong; Suzuki, Tetsuro; Zhou, Xianfeng (Frontiers in Oncology, 2025)
Lung cancer (LC) has been recognized as the leading cause of cancer mortality on a global scale. Although tobacco smoking is predominantly associated with LC (~85%), approximately 15-25% of lung cancers occur in non-smokers. This suggests that other biological cofactors, such as chronic infection and inflammation, are responsible for lung carcinogenesis. Due to the histological similarities between LC and Merkel cell polyomavirus (MCPyV)-associated Merkel cell carcinoma (MCC), studies have investigated their association, particularly small cell lung cancer (SCLC) and non-small cell lung cancer (NSCLC). However, the association between MCPyV infection and LC has been controversial due to inconsistent clinical findings in limited number of cases. To our knowledge, MCPyV is generally ubiquitous and maintains lifelong latent infections in immunocompetent individuals. Thus, its association with high-morbidity cancers raised concerns, and controversy about its cellular tropism as well. Further research is needed to elucidate the pathways by which MCPyV participates the development and progression of LC. Moreover, understanding the role of MCPyV in LC may lead to novel therapeutic strategies. In this review, we critically evaluate the available evidence for and against the aetiological association of MCPyV and LC to help understand its aetiological role, which will provide valuable insights for the diagnosis and therapy of LC.